Magnetization transfer contrast imaging detects early white matter changes in the APP/PS1 amyloidosis mouse model - Jelle Praet; Christian Bigot; Jasmien Orije; Maarten Naeyaert; Disha Shah; Zhenhua Mai; Pieter-Jan Guns; Annemie Van der Linden; Marleen Verhoye (NeuroImage: Clinical, 2016)
While no definitive cure for Alzheimer's disease exists yet, currently available treatments would benefit greatly from an earlier diagnosis. It has previously been shown that Magnetization transfer contrast (MTC) imaging is able to detect amyloid β plaques in old APP/PS1 mice. In the current study we investigated if MTC is also able to visualize early amyloid β (Aβ) induced pathological changes. In a cross-sectional study, a comparison was made between the MT ratio of wild type (WT) and APP/PS1 mice at 2, 4, 6, 8 and 24 months of age. We observed an increased MT-ratio in the cortex of 24 month old APP/PS1 mice as compared to WT mice. However, when comparing the MT-ratio of the cortex of WT mice with the MT-ratio of the APP/PS1 mice at 2, 4, 6 or 8 months of age, no significant changes could be observed. In contrast to the cortex, we consistently observed a decreased MT-ratio in the splenium of 4, 6 and 8 month old APP/PS1 mice as compared to age-matched WT mice. Lastly, the decreased MT-ratio in the splenium of APP/PS1 mice correlated to the Aβ plaque deposition, astrogliosis and microgliosis. This MT-ratio decrease did however not correlate to the myelin content. Combined, our results suggest that MTC is able to visualize early Aβ-induced changes in the splenium but not the cortex of APP/PS1 mice.